Pengembangan Instrumen Penilaian Kinerja Praktikum Organisasi Kehidupan Berbasis Konstruktivisme Kelas VII SMP: Development of Practical Performance Assessment Instrument for Class VII Middle School Constructivism-Based Life Organizations - Dewi Febrianty; Risnita Risnita; Afreni Hamidah (Universitas Jambi, 2017)
Practical performance assessment is an important part of the learning process, but several obstacles are found in its implementation. The objectives of this study are (1) to develop constructivism-based performance assessment instruments for class VII Yunior High School in Life Organization subject, (2) to describe aspects that need to be made in constructivism-based practical performance assessment instruments, and (3) to describe teacher responses in using constructivism-based practical performance assessment instruments. This research is a development research using a 4D model, the stages are defining, design, development and distribution. The trial subjects in this study consisted of 10 students for small group trials and 40 students for large group trials. The indicators used in the study include aspects related to the development of constructivist life-based practicum assessment instruments. Instrument used was a questionnaire to reveal the response of teachers and students to practical performance assessment instruments. The results of the data analysis showed that the content feasibility value is 86.31% at the intervals of 48.33 which means it is feasible to use. Most students gave a positive response to the assessment sheet given (96.67%), a small portion gave a negative response (33.3%). Because the average positive response of students is more than 75%, the performance assessment instrument is considered feasible to be applied.